Wizerunki Australii w twórczości i doświadczeniu migracyjnym Adama Fiali. Sytuacja pisarza polskiego na emigracji w Australii - Podemska-Abt, Teresa (Postscriptum Polonistyczne, 2020)
Along the lines of the socalled multicultural discourse and sociopolitical milieu in Australia, the article is concerned with Adam Fiala’s literary and nonliterary imageries of Australia and also deals with the relation of Fiala’s poetic and prose themes to various realities of Australia. Given that Australia as a host country determines/influences writers’ life and work, the article seeks to discover possible spaces in which the Polish writermigrant/his work and his characters/narrators/voices are positioned (and/or positioning themselves) to function and/or to domesticate Australia. Both the Polish writermigrant’s life in Australia and his literary scenarios are explained with some thought of migrancy and migrant/border narrative’ notions.